Jawabanmu

2014-01-25T13:30:29+07:00
5a = 24 + b
a =  \frac{24+b}{5}
a : b = 5 : 2
 \frac{ \frac{24 + b}{5} }{b} =  \frac{5}{2}
5b = 2 ( \frac{24+b}{5})
5b =  \frac{48+2b}{5}
25b = 48 + 2b
23 b = 48
b =  \frac{48}{23}

a =  \frac{24 + b}{5} =  \frac{24 +  \frac{48}{23} }{5} = \frac{ \frac{600}{23} }{5} =  \frac{600}{115}

c = 1/7 (a+b)
  = 1/7 (  \frac{600}{115} +  \frac{48}{23}
  = 1/7 (  \frac{19.320}{2645}
  =  \frac{19.320}{18.515}
2014-01-25T17:11:21+07:00
5a = 24 + b
a = 
a : b = 5 : 2

5b = 
5b = 
25b = 48 + 2b







23 b = 48
b = 
cari a
a =  = 
cari c
c = 1/7 (a+b)
  = 1/7 ( 
  = 1/7 ( 
  =